Comparative analysis of wild‐type accessions reveals novel determinants of Arabidopsis seed longevity. (23rd June 2022) - Niñoles, Regina; Planes, Dolores; Arjona, Paloma; Ruiz‐Pastor, Carmen; Chazarra, Rubén; Renard, Joan; Bueso, Eduardo; Forment, Javier; Serrano, Ramón; Kranner, Ilse; Roach, Thomas; Gadea, José
Abstract: Understanding the genetic factors involved in seed longevity is of paramount importance in agricultural and ecological contexts. The polygenic nature of this trait suggests that many of them remain undiscovered. Here, we exploited the contrasting seed longevity found amongst Arabidopsis thaliana accessions to further understand this phenomenon. Concentrations of glutathione were higher in longer‐lived than shorter‐lived accessions, supporting that redox poise plays a prominent role in seed longevity. However, high seed permeability, normally associated with shorter longevity, is also present in long‐lived accessions. Dry seed transcriptome analysis indicated that the contribution to longevity of stored messenger RNA (mRNAs) is complex, including mainly accession‐specific mechanisms. The detrimental effect on longevity caused by other factors may be counterbalanced by higher levels of specific mRNAs stored in dry seeds, for instance those of heat‐shock proteins. Indeed, loss‐of‐function mutant analysis demonstrated that heat‐shock factors HSF1A and 1B contributed to longevity. Furthermore, mutants of the stress‐granule zinc‐finger protein TZF9 or the spliceosome subunits MOS4 or MAC3A/MAC3B, extended seed longevity, positioning RNA as a novel player in the regulation of seed viability. mRNAs of proteins with putative relevance to longevity were also abundant in shorter‐lived accessions, reinforcing the idea that resistance to ageing is determined by multiple factors.